2004
DOI: 10.1145/986213.986239
|View full text |Cite
|
Sign up to set email alerts
|

Detecting money laundering and terrorist financing via data mining

Abstract: Using import-export information to improve financial transaction security.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…The imagery of money laundering may involve cross-border transfers, but we know little of how often this happens in practice: logically cross-border transfers should depend on the perceived risks and advantages of keeping funds within one's own jurisdiction (and preferences for investing elsewhere, especially for those with extended family abroad). But conceptually, concealment/ laundering can be achieved by transferring value by whatever means, including mispricing and mis-description of exported goods (Zdanowicz, 2004) or matching those businesspeople/tourists who want dollars or euros with those who have those currencies as proceeds of crime (Passas, 2003;FATF, 2006, APG, 2012Soudijn, 2014b). Such financial match-making can be undertaken by banks but it can also be done by semi-legitimate networks, usually (for trust and possible extra-legal recourse reasons) within the same ethnic or nationality group.…”
Section: How Are Proceeds Of Crime Concealed?mentioning
confidence: 99%
“…The imagery of money laundering may involve cross-border transfers, but we know little of how often this happens in practice: logically cross-border transfers should depend on the perceived risks and advantages of keeping funds within one's own jurisdiction (and preferences for investing elsewhere, especially for those with extended family abroad). But conceptually, concealment/ laundering can be achieved by transferring value by whatever means, including mispricing and mis-description of exported goods (Zdanowicz, 2004) or matching those businesspeople/tourists who want dollars or euros with those who have those currencies as proceeds of crime (Passas, 2003;FATF, 2006, APG, 2012Soudijn, 2014b). Such financial match-making can be undertaken by banks but it can also be done by semi-legitimate networks, usually (for trust and possible extra-legal recourse reasons) within the same ethnic or nationality group.…”
Section: How Are Proceeds Of Crime Concealed?mentioning
confidence: 99%
“…Since then researchers have investigated both machine-learning and traditional statistical approaches to detect money laundering (Irwin et al, 2012, Bidabad, 2017, Chang et al, 2008, Deng et al, 2009, Drezewski et al, 2012, Colladon and Remondi, 2017, Gilmour, 2017, Ju and Zheng, 2009, Ngai et al, 2011, Perols, 2011, Regan et al, 2017, Savage et al, 2016, Savage, 2017, Turner and Irwin, 2018, Unger et al, 2011, Wang et al, 2007, Zdanowicz, 2004a, Zdanowicz, 2009, Zhang et al, 2003, Gao, 2009). Zhang et al authors on using the system on real-world data found it was able to detect suspicious activity with a low rate of false positives.…”
Section: Detection Of Money Launderingmentioning
confidence: 99%
“…That is, if a customer is determined to have a network of many friends, a firm may reduce advertising costs by marketing to that pivotal customer and getting additional publicity for free, by word-of-mouth. On the other hand, analyses of bank deposits or of import/export data may detect possible money laundering or other criminal events [40]. The discovery of such patterns might lead to preventative measures.…”
Section: Conducting Relevant Research In Computer Sciencementioning
confidence: 99%